The sleep–wake history contributes to rhythmic BMAL1 chromatin binding in the cerebral cortex but not in the liver - Carlos Neves; Charlotte N. Hor; Sonia Jimenez; Paul Franken (Proceedings of the National Academy of Sciences, 2025)
The timing and quality of sleep is regulated by circadian- and sleep–wake-driven processes. The core clock gene Bmal1 not only affects the circadian timing of sleep, but also the response to sleep deprivation (SD), which, in turn, causes long-term changes in cortical Bmal1 expression. We aimed at separating the circadian- and sleep–wake-driven contributions to BMAL1 binding to its target genes in the cerebral cortex by scheduling 6 SDs at 4 h intervals across the daily 12 h light/12 h dark cycle. We show that BMAL1 rhythmically bound its tissue-specific targets with tissue-specific dynamics, reaching peak binding 2 to 4 h later in the cortex than in the liver, while trough times did not differ. The SDs affected BMAL1 binding most significantly in the cortex, causing 80% of rhythmically bound regions to lose rhythmicity, suggesting BMAL1 binding has a prominent sleep–wake-driven component in this tissue. Analyses of the promoters of other core clock-genes indicate that BMAL1 binding to Bhlhe41 and Nr2d1 have a strong sleep–wake-driven component, while for Per2 two binding regions were identified one with circadian- and the other with sleep–wake-driven binding dynamics. Our results attest to a nonadditive interaction of time-of-day and time-spent-awake affecting the core molecular circadian circuitry. It further highlights that rhythms in gene expression in peripheral tissues are an emergent property of molecular interactions beyond that of the core molecular clock circuitry.